Peran Inventory Intencity dalam Determinasi Harga Saham Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2022 - Dimyati, Muhaimin; Fitria Ningsih, Wiwik (Institut Teknologi dan Sains Mandala, 2024)
Indonesia's economic growth is expected to continue to accelerate until 2024, which is expected to reach 6.5%. This forecast is influenced by a number of indicators both global and domestic. One of them is the economic growth of major trading partners in the second quarter of 2022, which continued to experience growth, although it slowed from the previous quarter. Economic growth, which shows a positive trend, also illustrates that the investment climate in Indonesia is increasingly conducive and developing. This can also be seen from the development of the number of investors listed on the Jakarta Stock Exchange. An investor, before investing must analyze the condition and financial statements of a company, where the company's financial statements usually guarantee the condition of development or success or failure of a company. Stock is a sign of ownership of a person or entity in a company (Sunariyah, 2006). There is one thing that must always be remembered in investing in stocks, that high profits are also followed by high risks as well. In investment there are two risks, namely systematic risk and unsystematic risk. Risks that always exist and cannot be eliminated by diversification are referred to as systematic risks. To analyze the determinants of stock prices is done by regression analysis without and with moderation variables. Based on the results of testing the coefficient of determination (R2) in the regression model without the moderation variable, a coefficient of determination value of 0.146 was obtained in model 5, there is only one independent variable left, namely ROA. This figure shows the amount of contribution of the independent variable Return On Assets to stock price variations is 14.60%. While the value of the coefficient of determination in the regression model with moderation variables, obtained a coefficient of determination value of 0.304 in model 3, with four independent variables, namely Capital Intencity (CI), Inventory Intencity (II), Return On Assets (ROA), and Capital Intencity variables moderated by Inventory Intencity variables. This figure shows the amount of independent variable contribution to stock price variations is 30.40%. This result is far from the standard role of the independent variable to the variation of the dependent variable which is 75%.